Penyelesaian Konflik Rumah Tangga Perspektif QS. al-Nisā’/4: 35 - Nur Afni Handayani; Halimah Basri; Ahmad Mujahid (Khidmatussifa: Journal of Islamic Studies, 2025)
The increasing number of problems and conflicts in household life shows the importance of resolution efforts that are able to maintain family unity in a wise and peaceful manner. This study aims to examine the concept of household conflict mediation from the perspective of QS. al-Nisā’/4:35. This research employs a qualitative approach using the library research method. Primary data were obtained from classical and contemporary Qur’anic exegesis books, while secondary data were collected from books and scientific articles related to household conflict, mediation, and Islamic family law. The data were analyzed using a descriptive-analytical method through a tahlili interpretation approach to QS. al-Nisā’/4:35. The findings reveal that household conflict (syiqāq) is a condition of dispute between husband and wife that may threaten family stability if not properly managed. The Qur’an offers a conflict resolution mechanism through the appointment of two ḥakam from both families as mediators to achieve iṣlāḥ (reconciliation). This study concludes that QS. al-Nisā’/4:35 not only provides a normative solution to household conflicts but also offers an applicable and contextual mediation model for maintaining family harmony amid the dynamics of modern life.